Dampak Silaturahim Pada Kinerja Usaha Anggota HIPMI Surabaya - Kumajaya, Gandhi Satrya; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Research aims to know impact silaturahim performance business members HIPMI Surabaya. This research use qualitative approach and kind of his research use eksplanatori. This research use the kind of research eksplanatori for want of analyzing relation between one variable other variables or how can a variables affecting other variables. Strategy used in this research is case study.The result showed that silaturahim between members HIPMI Surabaya able to create social interaction or interpersonal communication. The more interpersonal communication process for entrepreneurs, then synergy between employers who one by another be interwoven. Synergy the can bring business cooperation and increase knowledge about business itself. Those things that influences the performance business members HIPMI Surabaya. Increasing the efforts can be seen through increased turnover, profit, value, of market share, and labor owned entrepreneurs who belongs to a HIPMI Surabaya.